2006
DOI: 10.1038/sj.bjp.0706642
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium‐dependent relaxation evoked by ATP and UTP in the aorta of P2Y2‐deficient mice

Abstract: 1 Based on pharmacological criteria, we previously suggested that in the mouse aorta, endotheliumdependent relaxation by nucleotides is mediated by P2Y 1 (adenosine diphosphate (ADP)), P2Y 2 (adenosine triphosphate (ATP)) and P2Y 6 (uridine diphosphate (UDP)) receptors. For UTP, it was unclear whether P2Y 2 , P2Y 6 or yet another subtype was involved. Therefore, in view of the lack of selective purinergic agonists and antagonists, we used P2Y 2 -deficient mice to clarify the action of UTP. 2 Thoracic aorta seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
56
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 27 publications
6
56
0
1
Order By: Relevance
“…However, recent studies on the mouse aorta revealed in an unexpected way that although the endotheliumdependent relaxation by ATP was severely decreased in P2Y 2 Ϫ/Ϫ mice, the relaxing effect of UTP was maintained, indicating the involvement of another receptor (Guns et al, 2006). This receptor might be P2Y 6 because UDP induced a relaxing effect on the mouse aorta with pharmacological features compatible with that receptor (Guns et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, recent studies on the mouse aorta revealed in an unexpected way that although the endotheliumdependent relaxation by ATP was severely decreased in P2Y 2 Ϫ/Ϫ mice, the relaxing effect of UTP was maintained, indicating the involvement of another receptor (Guns et al, 2006). This receptor might be P2Y 6 because UDP induced a relaxing effect on the mouse aorta with pharmacological features compatible with that receptor (Guns et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, UDP is a growth factor for aortic smooth muscle cells in vitro (Hou et al, 2002). UDP induced an endothelium-dependent relaxation of the mouse aorta, which, like a similar action of UTP, was maintained in P2Y 2 Ϫ/Ϫ mice, suggesting the possible involvement of the P2Y 6 receptor (Guns et al, 2005(Guns et al, , 2006.…”
mentioning
confidence: 84%
“…Such a dual role has already been reported for another P2Y receptor subtype, P2Y 2 . This receptor contributes to endothelium-dependent relaxation 39 and to the expression of VCAM-1, which mediates the adhesion of monocytes to vascular endothelium. 40 The atherosclerotic lesions of P2Y 1 Ϫ/Ϫ /ApoE Ϫ/Ϫ mice also contained fewer smooth muscle cells than those of ApoE Ϫ/Ϫ mice, indicating that P2Y 1 receptor deficiency might influence the behavior of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from both basic research and clinical studies indicates that purinergic signaling plays an important role in the atherosclerotic process. Guns et al found that in the aorta of P2Y2-knockout mice, there was inhibition of the ATP-endothelium-dependent relaxation, 9 which substantiates the role of P2RY2 in endothelial dysfunction. A recent study also reported that upregulation and activation of P2RY2 in rabbit arteries mediates the intimal hyperplasia that accompanies atherosclerosis, 10 further confirming a direct pathological role for P2RY2.…”
mentioning
confidence: 86%